2006
DOI: 10.1177/0148607106030002124
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Fatty Acid Composition and Diamine Oxidase Activity of Intestinal Mucosa From Rats Treated With Irinotecan Hydrochloride (CPT‐11) under Vegetable Oil–Enriched Diets: Comparison Between Perilla Oil and Corn Oil

Abstract: CPT-11 induced changes of intestinal mucosal fatty acid composition with increased PGE(2) level and decreased intestinal integrity; perilla oil shows the possibility of being able to attenuate those changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…When intestinal mucosal epidermis is damaged, DAO is released into blood, indicating that DAO in blood reflects the destruction of the intestinal mucosal epithelial cell layer and intestinal mucosa barricade [14,15] . In our study, DAO was localized mostly in the epithelial cell layer of mucous membrane as previously described [16] , and Lianshu preparation could effectively decrease DAO induced by LPS. However, its mechanism of action remains unclear.…”
supporting
confidence: 74%
“…When intestinal mucosal epidermis is damaged, DAO is released into blood, indicating that DAO in blood reflects the destruction of the intestinal mucosal epithelial cell layer and intestinal mucosa barricade [14,15] . In our study, DAO was localized mostly in the epithelial cell layer of mucous membrane as previously described [16] , and Lianshu preparation could effectively decrease DAO induced by LPS. However, its mechanism of action remains unclear.…”
supporting
confidence: 74%
“…Other reports have also shown that supplementation with ALA-rich perilla oil resulted in a significant increase of ALA and EPA in the colon mucosa of rats treated with CPT-11, an anticancer drug (17). Whereas conversion of ALA into EPA and DHA is still greatly debated in humans (34), a previous study has shown that supplementation with camelina oil significantly increased serum ALA, EPA, and DHA concentrations in hypercholesterolemic patients (35).…”
Section: Discussionmentioning
confidence: 93%
“…Rats received either an (n-3) PUFA diet (TNBS+ALA group, 450 mg×kg 21 ×d 21 ) or corn oil diet (control and TNBS groups). The diets were isocaloric and corn oil was chosen as a control diet because of its current use in many studies using dietary ALA-rich oils such as flaxseed oil (16) or perilla oil (17). Rats were feed deprived for 24 h prior to induction of colitis and were allowed free access to tap water throughout the study.…”
Section: Dietmentioning
confidence: 99%
“…The enzyme reaction was stopped by the addition of 0.5 ml 30 mmol/l sodium diethyldithiocarbamate, and absorbance was measured at 668 nm. 16 Protein concentrations of leptin in the tissue homogenate were measured by enzyme immunosorbent assay (ELISA) kits (code no. 27295; IBL, Gunma, Japan) according to the manufacturer's instructions.…”
Section: Dao Activity and Protein Concentrations Of Leptin In The Smamentioning
confidence: 99%